MUTU PELAYANAN PETUGAS REKAM MEDIS TERHADAP TINGKAT KEPUASAN PASIEN BPJS RAWAT JALAN DI RUMAH SAKIT UMUM IPI MEDAN TAHUN 2019 - Johanna Christy (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2020)
Quality of service is the overall characteristics of the service that shows its ability to satisfy the needs of consumers, and the Health BPJS is a legal entity formed to carry out a health insurance program, and patient satisfaction is the level of patient feelings that arise as a result of the performance of health services obtained after the patient compares it with what he hoped for. The purpose of this study was to determine the quality of medical record officer services to the level of satisfaction of outpatient BPJS patients in General Hospital. IPI Medan 2018. This research uses Analytical research design. The independent variable is BPJS Health service quality and the dependent variable is patient satisfaction. Samples taken using the Slovin Formula found 33 patients in the Outpatient Installation at the General Hospital. IPI. Medan in 2018. The research instrument used a questionnaire. The results showed that 28 respondents (84.8%) stated that the quality of BPJS Health services was good, and 32% of respondents (97.0%) expressed satisfaction with BPJS Health services. Chi Square statistical test results state there is a relationship between the quality of BPJS Health services with patient satisfaction Outpatient Installation at the General Hospital. IPI. Medan Year 2018 (pValue = 0,000). The implication of the results of the study shows that the quality of BPJS Health services has an important role in influencing patient satisfaction.